2016
DOI: 10.1111/jpn.12493
|View full text |Cite
|
Sign up to set email alerts
|

Feeding different dietary protein to energy ratios to Holstein heifers: effects on growth performance, blood metabolites and rumen fermentation parameters

Abstract: Eighteen Chinese Holstein heifers average age 230 ± 14 days were allocated to 1 of 3 dietary crude protein (CP) to metabolizable energy (ME) ratios to examine the effects on growth performance, blood metabolites and rumen fermentation parameters with 90-days experiment. Three different dietary CP:ME ratios were targeted based on the formulation of dietary CP contents of 10.85%, 12.78% and 14.63% on dry matter (DM) basis with similar ME contents (10.42 MJ/kg DM), which were categorized as low, medium and high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 28 publications
5
16
1
Order By: Relevance
“…This result support the previous report of Serment et al (2011). Abonyi et al (2013), Chen et al (2015) and Dong et al (2017) who revealed that the high concentrate diet probably improved energy balance, protein synthesis and humoral immunity of the animal. Blood urea nitrogen (BUN) concentration was used as indicator of nitrogen utilization efficiency by ruminants (Lewis, 1957).…”
Section: Blood Metabolitessupporting
confidence: 92%
“…This result support the previous report of Serment et al (2011). Abonyi et al (2013), Chen et al (2015) and Dong et al (2017) who revealed that the high concentrate diet probably improved energy balance, protein synthesis and humoral immunity of the animal. Blood urea nitrogen (BUN) concentration was used as indicator of nitrogen utilization efficiency by ruminants (Lewis, 1957).…”
Section: Blood Metabolitessupporting
confidence: 92%
“…In rats, direct comparison of a high versus low protein diet during pregnancy and lactation revealed higher growth rates in the offspring in a sex-specific manner (Thone-Reineke et al 2006 ). The protein-to-energy ratio also was demonstrated in non-rodent animals as an important determinant of weight gain (Garling and Wilson 1976 ; Dong et al 2017 ). An excess of protein intake in mice by means of a 40% protein diet, impaired postnatal growth (Kucia et al 2011 ), supporting a major effect of macronutrient composition also in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the CPI/MEI was the lowest in P3, suggesting an imbalance of dietary CP/ ME. It is suggested that nitrogen utilization in ruminants is influenced by dietary ME and CP content, as well as their proportion (Dong et al 2017), while the liver is the important organ in nitrogen utilization. Thus, several amino acids and amino acid metabolism-related metabolites were observed to decrease in liver in P3.…”
Section: Discussionmentioning
confidence: 99%